The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22452/mjlis.vol24no1.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating academics’ knowledge sharing intentions in Malaysian public universities

Abstract: Academics are the pillars of Institutions of Higher Learning (IHLs) where knowledge is created and shared. Willing academics will determine the quality of knowledge being shared between themselves and their students. In this research, a pilot study is conducted among academics in public IHLs, whereby the theory of planned behaviour (TPB) is adapted to study the academics' intention to share. Responses are obtained from 45 academics out of 399 survey questionnaires sent via email. This study uses the partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 58 publications
3
36
0
2
Order By: Relevance
“…Furthermore, our results align with current research on knowledge transfer in higher education institutions. Using a questionnaire design, Fauzi et al (2019) demonstrated that social networks positively influenced knowledge sharing attitudes, which positively influenced the knowledge sharing intention of academics in turn. We have expanded the current research through quantitative structural SNA, demonstrating that social networks in higher education (especially educational innovation networks) can be created and supported through networking interventions that support knowledge transfer and innovation diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results align with current research on knowledge transfer in higher education institutions. Using a questionnaire design, Fauzi et al (2019) demonstrated that social networks positively influenced knowledge sharing attitudes, which positively influenced the knowledge sharing intention of academics in turn. We have expanded the current research through quantitative structural SNA, demonstrating that social networks in higher education (especially educational innovation networks) can be created and supported through networking interventions that support knowledge transfer and innovation diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that knowledge sharing is an important aspect that motivates individuals to enhance entrepreneurial behaviour (Hormiga et al, 2016;De Clercq et al, 2013;Castro, Nagano, & Ribeiro, 2019). Many argue that knowledge sharing should be practiced and developed into a culture and norm in higher education as it is the place where knowledge is disseminated and celebrated (Fauzi, Tan, Thurasamy, & Ojo, 2019c). All the four variables of transformational leadership are predicted to have positive significant impact on knowledge sharing.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…It is undeniable that the emergence of cryptocurrency will play a significant role in the world's economic fabric. It is the fact that every economist, researchers, investors alike has to act and considerable measures to strengthen their knowledge on the blockchain technology in general (Fauzi et al, 2019;Fauzi et al, 2018a). As cryptocurrency has not yet reached maturity in term of time frame, further studies on its technology, potential and risk should be studied to ensure that the opportunities are not just a mere fluke.…”
Section: Improvement and Future Work On Cryptocurrenciesmentioning
confidence: 99%